Studi Literatur : Penambatan Senyawa Komponen Tanaman Kumis Kucing ( Orthosiphon Stamineus Benth ) Sebagai Diuretik Menggunakan Metode Docking - Sefira Novi Ariyanto; Saeful Amin; Eva Sucianti; Fitria Mutiara Rohmah (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Orthosiphon stamineus Benth., commonly known as kumis kucing, is a widely recognized medicinal herb in traditional medicine, particularly valued for its diuretic properties. This study aims to evaluate the potential of active compounds in O. stamineus as diuretic agents through an in silico approach using molecular docking methods. A total of 98 compounds were screened against three diuretic target receptors: 1Z9Y (furosemide receptor), 3HS4 (acetazolamide receptor), and 3VHU (spironolactone receptor). The docking results revealed that lithospermic acid I, dicaffeoyl tartaric acid, and orthosiponone C exhibited lower binding energies compared to standard ligands, indicating higher affinity and stronger molecular interaction stability. Molecular visualization showed that these compounds formed specific interactions, such as hydrogen bonds and π-π stacking, resembling the binding mechanisms of synthetic diuretics. This study highlights the significant potential of O. stamineus to be developed into a natural diuretic phytopharmaceutical. However, further validation through in vitro and in vivo studies is necessary to confirm their efficacy and safety in complex biological systems.